Managing Key Performance Indicators (KPIs): A case study at an aerospace manufacturing facility - Abdullah, Rohana; Mohamad, Effendi; Muhamad, Mohd Razali (2008)
Key Performance Indicators (KPIs) is a performance measurement tools that an Aerospace Manufacturing facility has decided to implement in order to remain cost competitive. Since KPIs was a new concept that the company was embracing, the challenge was on managing the KPIs throughout the entire organization.This study is focused on the planning, designing, and implementing the KPIs project.Methodologies such as the semi-structure interview, focus group discussion, benchmarking were used in order to identify the gap, prepare crucial information for the development of the KPIs and gauge KPIs knowledge level of the top management who are going to be responsible for the development and deployment of the company’s KPIs. Results of a successful KPIs design and deployement will also be discussed in this paper.